An Efficient Method to Discover Transformed Data Leak - Sindhuja, S; Valliammai, M (International Journal of Computer Sciences and Engineering, 2025)
The computer system poses a serious threat to the organisational security due to the leak of sensitive data. According to the report of risk based security (RBS), the leaked sensitive data records has increased dramatically during last few years, (i.e.) from 412 million in 2012 to 822 million in 2013. These are caused only by the lack of proper encryption on files and documents and by human errors these causes data loss. Organisation has the responsibility of screening the content which is stored in the system as sensitive data. In this paper, we utilize two techniques, which are levenshtein-distance technique and luecene search framework. These two helps to detect the leakage of data and this technique is used for screening the data which are outsourced and it also keep an track of, who is transferring the data